La Corte Constitucional ecuatoriana en la gobernanza del riesgo ante la COVID-19 (Tema Central) - Cahueñas Muñoz, Hugo (2021)
Based on a disaster risk governance approach, the article analyzes the rulings of the Constitutional Court before the states of exception adopted against COVID-19 until November 2020. The analysis is divided into two moments: a) the first rulings, where the Court presents exhorts and recommendations; and, b) opinion No. 5-20-EE / 20 where an ultimatum is placed on the decrees of states of exception, and an ordinary regime to respond to COVID-19 is required. Additionally, in the last ruling, the Constitutional Court identifies normative and institutional frameworks through which the response to COVID-19 can be managed once the state of exception has concluded. However, the Court also calls for a law to respond to the pandemic. Under a disaster risk governance approach, it is imperative to adopt a legal and institutional framework for the comprehensive management of disaster risks, not only due to COVID-19, but generally, an ordinary regime that allows strengthening capacities and reduce vulnerabilities to disaster risks. Similarly, in future constitutionality rulings related to disasters, the Constitutional Court must take into account the international parameters of disaster risk reduction.